Design and Implementation of an ESP32-Based Object Tracking Robot Using Ultrasonic and Infrared Sensors - Syahrul, Elfitrin; Riefqi, Achmad; Yapie, Any Kurniawaty (Jurusan Teknik Elektro Fakultas Teknik Universitas Sriwijaya, 2026)
Abstract— This paper presents the design and implementation of an ESP32-based autonomous tracking robot that integrates ultrasonic and infrared sensing for target following and edge avoidance. The system utilizes HC-SR04 and HC-SR04P ultrasonic sensors mounted at the front, left, and right to estimate target distance, while infrared sensors detect floor edges to prevent accidental drop-offs. A dual-L298N motor driver configuration controls four DC motors, enabling real-time movement execution based on sensor feedback. Experimental testing shows that the ultrasonic modules achieved distance-measurement accuracy with an error rate of 1–5%. The infrared sensors reliably detected edges, with performance influenced by surface reflectivity. The integrated control system executed forward, reverse, turning, and stop maneuvers effectively in dynamic target-tracking scenarios. These results indicate that combining ultrasonic and infrared sensing with an ESP32 controller provides a functional, low-cost solution for autonomous tracking in constrained indoor environments.